Sessile serrated lesion prevalence and factors associated with their detection: a post-hoc analysis of a multinational randomized controlled trial from Asia - Tan, Chin Kimg; Suzuki, Sho; Ang, Tiing Leong; Koh, Xuan Han; Wang, Lai Mun; Aniwan, Satimai; Chiu, Han-Mo; Laohavichitra, Kannikar; Chirapongsathorn, Sakkarin; Yamamura, Takeshi; Kuo, Chen Ya; Yoshida, Naohisa; Takezawa, Takahito; Rerknimitr, Rungsun; Ishikawa, Hideki; Gotoda, Takuji (Endoscopy, 2024)
Background Sessile serrated lesions (SSLs) are associated with an increased risk of colorectal cancer. Data on the prevalence of SSLs in Asia are limited. We performed this study to estimate the prevalence of SSLs in Asia and to explore endoscopic factors that are associated with SSL detection.Methods This is a post-hoc analysis of a multicenter randomized controlled trial from four Asian countries/regions that compared adenoma detection rates using linked-color imaging (LCI) and white-light imaging. Colonoscopies were performed in an average-risk population for screening, diagnostic examination, or polyp surveillance. Patients with SSLs were compared against those without SSLs to evaluate for possible predictors of SSL detection using Firth’s logistic regression.Results 2898 participants (mean age 64.5 years) were included in the analysis. The estimated prevalence of SSLs was 4.0% (95%CI 3.4%–4.8%), with no sex or age group differences. On multivariable analysis, use of LCI (adjusted odds ratio [aOR] 1.63, 95%CI 1.10–2.41), experienced endoscopists (aOR 1.94, 95%CI 1.25–3.00), use of transparent cap (aOR 1.75, 95%CI 1.09–2.81), and longer withdrawal time (aOR 1.06, 95%CI 1.03–1.10) were independently associated with SSL detection. Synchronous adenoma detection (aOR 1.89, 95%CI 1.20–2.99) was also predictive of SSL detection.Conclusion The prevalence of SSLs in Asia is 4.0%. Use of LCI or a transparent cap, greater endoscopist experience, and longer withdrawal time were all associated with increased SSL detection.